CONDITIONS OPTIMIZATION OF GINGEROL EXTRACTION FROM RED GINGER (ZINGIBER OFFICINALE ROSCOE VAR. SUNTI VAL) BY SUPERCRITICAL FLUID EXTRACTION - Sofia Binti Suhaimy, Ainin
Determination of the plant was done in Herbarium Bandungense, The School of Life Science and Technology, Bandung Institute of Technology. The result of determination confirmed that the plant used was Zingiber officinale Roscoe var. sunti Val from Zingeberacea family. The crude drug was characterized for its water content which was 9.62 % v/w, total ash content 5.37 % w/w, acid insoluble ash content 1.92 % w/w, water soluble extractable matter 14.85 % w/w, ethanol soluble extractable matter 4.68 % w/w and loss of drying 9.9 %. Phytochemical screening results of crude drug showed the presence of flavonoid, tannin and phenol. The fresh rhizomes of the red ginger were collected, dried and powdered, and then stored in a dried, well-closed container and away from direct light. The crude drug was weighed and then placed inside the extraction vessel of R-401 Supercritical Fluid Extraction (SFE) system instrument provided in lab. The supercritical fluid used was supercritical carbon dioxide. The machinery was let to stabilize for 2 hours and then let to run at conditions of different temperature (°C) and pressure (bar) crossovers which were 35 °C 120 bar, 35 °C 160 bar, 35 °C 200 bar, 65 °C 120 bar, 65 °C 160 bar, 65 °C 200 bar, 95 °C 120 bar, 95 °C 160 bar and 95 °C 200 bar. The extraction was performed for 2 hours and each extraction of one condition was repeated for 3 times for total of 27 oil products. Both of gingerol standard solutions and sample solutions were prepared with chloroform and spotted on TLC plate GF254 by Linomat 5, then let to be developed inside the chamber with toluene: ethyl actetate (9:1) as mobile phase. The dried plate was placed inside TLC scanner 3 and the wavelength set was 239 nm. The Area under the curve (AUC) of peaks which were detected at specific Rf were taken. The AUC-mass graph was plotted to obtain the linear regression to calculate the gingerol content of each sample in percentage. The result from analysis showed that the highest amount of gingerol content in Zingiber officinale Roscoe var. sunti Val was at at 95 °C 200 bar with the value of 0.28%. This was due to that at high pressure and temperature, supercritical fluid increases in density hence was able to diffuse through solid like a gas and dissolve gingerol like a liquid. Furthermore, the diffusion power was maximized and hence increased the solubility of gingerol into supercritical fluid.